Location of R&D activities by vertical multinationals over asymmetric countries - Silva, Carlos Eduardo Lobo e (2018)
This paper deals with the location of R&D by vertical multinational firms. By taking the colocation of laboratories and productive plants as a benchmark, we can see that the spatial separation of both emerges under two conditions – high intensity of R&D spillovers and strong size asymmetry between countries. The latter condition is effective since it is related with a rising international inequality of wages. If the spatial separation of R&D and manufacturing takes place, headquarters services (namely R&D units) will be likely located in the smaller country. The converse pattern, where laboratories are place in the larger country, may arise if production is high-tech and the localized externalities of research activity are strong. Hence, this article confirms the main results of the literature on this topic but in the context of a different framework which allows us to tackle two usually disregarded topics: the transfer cost of technology; and the direct engagement of industrial workers in R&D spillovers. These aspects are dealt with by presupposing that, in addition to a “technological” externality among researchers, there is an “educational” externality exerted by researchers upon neighbouring industrial workers. When a country loses its laboratories, the inhabitants become intellectually “impoverished” and their labour starts to have a lesser efficiency.